Health-awareness of Saudi Consumers and its Mediating Impact on The Effect of Marketing Mix Strategy on Purchasing Food Online during COVID-19 - Alsheikh, Layla Hodaed; Alsheikh, Dalal Hodaed (The Arab Journal of Administration, 2025)
This study aims to explore the mediating impact of health awareness of Saudi consumers on the relationship between the marketing strategy of online food retailers and food purchasing decisions during the Covid-19 period. The study employs the marketing mix model (price, product, place and promotion) to analyse its impact on purchasing decisions. Health awareness of consumers is regarded as a mediating factor. The data are collected from consumers of online food retailers using an online questionnaire. 465 respondents completed the questionnaire. The results show that the marketing mix elements of the marketing strategy have a positive impact on purchasing decisions except for the price of the product. When looking at the impact of marketing strategy on health awareness among consumers, only the promotion does not have a statistically significant impact on consumer’s health awareness. The study also revealed a significant relation between consumer’s health awareness and purchasing decisions. Lastly, health awareness partially mediates the impact of marketing strategy on purchasing decision. The findings have several implications for both practitioners (retailers) and academics. The study concludes with future research recommendations with focus on segmentation of respondents on age, gender and economic status.